Symbolic Active Rc Circuit Synthesis Using Matlab - Waldecker, Miroslav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
Implementation of the procedure for synthesis of the active RC circuit from prescribed transfer function using MATLAB (R) , without prior knowledge of topology or circuit architecture is presented. Method is based on the reverse process of a Gaussian pivotal elimination applied to nodal admittance matrix as proposed in [6]. This method is very useful for searching alternative circuits realizations of the same transfer function, or with modifications to find several even all realizations in some level. Given implementation has several limitations like specific input transfer function format and interaction with human for further decisions in the synthesis process.
Keywords: Nullors; Active-RC; Synthesis; Admittance matrix